Numerical simulation of magneto thermal Marangoni convective flow of dusty Sutterby hybrid nanofluid with variable thermal conductivity - Abbas, Munawar; Khan, Nargis; Hashmi, Muhammad Sadiq; İnç, Mustafa (Wiley-V C H Verlag Gmbh, 2024)
The current study concentrated on the 2-D flow of a dusty, Magnetohydrodynamics (MHD) Sutterby hybrid nanofluid flowing across a surface in a Darcy-Forchheimer medium. The Cattaneo-Christov heat flux model and variable thermal conductivity properties are taken into description. Marangoni convective boundary conditions are taken into consideration while the thermal flow analysis is examined. Some of the applications of Marangoni convection include thin-film diffusion, the formation of molten crystals, semiconductor fabrication, and the growth of vapor bubbles during nucleation. Hybrid nanofluid is made up of two nanoparticles (Ag - Cu) and one base fluid C2H6O2. Determining the Marangoni convective flow of dusty hybrid nanofluid thermal mobility with ethylene glycol base fluids is the main objective of this investigation. The accepted nanoparticles and dust particles are assigned a spherical shape. The problem has been modeled using nonlinear partial differential equations. With the use of transformation, the partial differential equations (PDEs) system is reduced to a set of ordinary differential equation (ODEs). The problem is mathematically stated, and then using the RKF-45th approach, it is numerically solved. Tables and graphs are used to assess the effects of the physical parameters of the current problem, such as the Deborah number, Eckert number and thermal relaxation parameter. The thickness of the momentum boundary layer decreases by growing the inverse Darcy number and the Forchheimer parameter for both phases. The velocity profiles of the dust and fluid phases are improved by greater estimates of the Deborah number.
Keywords: Radiative Heat-Transfer; Mhd Flow; Fluid; Nanoparticles; Surface; Model